Cecal ligation and puncture followed by MRSA pneumonia increases mortality in mice and blunts production of local and systemic cytokines - Jung, Enjae (2012)
Mortality in the ICU frequently results from the synergistic effect of two temporally-distinct infections. This study examined the pathophysiology of a new model of intraabdominal sepsis followed by methicillin-resistant Staphylococcus aureus (MRSA) pneumonia. Mice underwent cecal ligation and puncture (CLP) or sham laparotomy followed three days later by an intratracheal injection of MRSA or saline. Both CLP/saline and sham/MRSA mice had 100% survival while animals with CLP followed by MRSA pneumonia had 67% seven-day survival. Animals subjected to CLP/MRSA had increased bronchoalveolar lavage (BAL) concentrations of MRSA compared to sham/MRSA animals. Animals subjected to sham/MRSA pneumonia had increased BAL levels of IL-6, TNF-α, and G-CSF compared to those given intratracheal saline while CLP/MRSA mice had a blunted local inflammatory response with markedly decreased cytokine levels. Similarly, animals subjected to CLP/saline had increased peritoneal lavage levels of IL-6 and IL-1β compared to those subjected to sham laparotomy while this response was blunted in CLP/MRSA mice. Systemic cytokines were upregulated in both CLP/saline and sham/MRSA mice, and this was blunted by the combination of CLP/MRSA. In contrast, no synergistic effect on pneumonia severity, white blood cell count or lymphocyte apoptosis was identified in CLP/MRSA mice compared to animals with either insult in isolation. These results indicate that a clinically relevant model of CLP followed by MRSA pneumonia causes higher mortality than could have been predicted from studying either infection in isolation, and this was associated with a blunted local (pulmonary and peritoneal) and systemic inflammatory response and decreased ability to clear infection.